2016
DOI: 10.5530/pj.2017.1.14
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS headspace analysis of Terminalia ferdinandiana fruit and leaf extracts which inhibit Bacillus anthracis growth

Abstract: Background:Terminalia ferdinandiana (Kakadu plum) is an endemic Australian plant with an extremely high antioxidant capacity. The fruit has long been used by the first Australians as a nutritional food and as a medicine and recent studies have reported its potent growth inhibitory activity against a broad panel of bacteria. Despite this, T. ferdinandiana extracts are yet to be tested for the ability to inhibit the growth of Bacillus anthracis. Materials and Methods: Solvent extracts were prepared using both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 23 publications
(37 reference statements)
0
38
0
Order By: Relevance
“…Interestingly, high ascorbic acid content is a characteristic observed in all Terminalia spp. [11] and previous studies have reported that the toxicity of Indian [15,16], Australian [12,14,21,25] and South African Terminalia spp. [17,18] correlates with their high ascorbic acid content.…”
Section: Quantification Of Toxicitymentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, high ascorbic acid content is a characteristic observed in all Terminalia spp. [11] and previous studies have reported that the toxicity of Indian [15,16], Australian [12,14,21,25] and South African Terminalia spp. [17,18] correlates with their high ascorbic acid content.…”
Section: Quantification Of Toxicitymentioning
confidence: 85%
“…Filter discs infused with 10 µL of distilled water were used as a negative control. Minimum inhibitory concentrations (MICs) of each extract were also assessed by disc diffusion assay as previously described [21]. Briefly, the extracts were diluted in deionized water and tested across a range of concentrations.…”
Section: Evaluation Of Antibacterial Activitymentioning
confidence: 99%
“…Toxicity of the E. officinalis fruit extracts, the reference toxin and the conventional antibiotics was assessed using a modified Artemia franciscana nauplii lethality assay. [27][28][29] The LC 50 with 95% confidence limits for each treatment was calculated using probit analysis.…”
Section: Artemia Franciscana Kellogg Nauplii Toxicity Screeningmentioning
confidence: 99%
“…26,27 Briefly, 400 µL of seawater containing ~43 (mean 43.2, n = 155, SD 14.5) A. franciscana nauplii were added to wells of a 48 well plate and immediately used in the bioassay. Volumes of 400 µL of reference toxin or the diluted plant extracts were transferred to the wells and incubated at 25 ± 1 °C under artificial light (1000 Lux).…”
Section: Artemia Franciscana Nauplii Toxicity Screeningmentioning
confidence: 99%